Soviet samizdat periodicals : uncensored texts of the late soviet era - University of Toronto - Library (2022)
Soviet Samizdat Periodicals is a database of information about editions of classic Soviet samizdat, 1956-1986. The Database includes approximately 300 titles, representing all known types of samizdat periodical editions from this late Soviet era, including human rights bulletins, poetry anthologies, rock zines, religious and national editions. Researchers will find detailed bibliographic and archival information. The site also includes information about samizdat and dissidence for the general public.